2013
DOI: 10.1136/tobaccocontrol-2013-050989
|View full text |Cite
|
Sign up to set email alerts
|

An endgame for tobacco?

Abstract: Since its origins in the 1960s, tobacco control has achieved remarkable success against the scourge of tobacco-produced disease and death. Yet tobacco use, especially cigarette smoking, remains the world's leading cause of preventable premature death and is likely to do so for decades to come. Evidence-based policies seem incapable of substantially hastening the demise of smoking. Slowness in the decline of smoking in developed nations, and increasing smoking in many low- and middle-income countries has sparke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 27 publications
1
58
0
Order By: Relevance
“…Smoking remains one of the most common risk behaviors worldwide, despite all that is known about its detrimental effects on many diverse aspects of human health (5). Many studies have shown that smoking also affects bone health in a negative fashion (6).…”
mentioning
confidence: 99%
“…Smoking remains one of the most common risk behaviors worldwide, despite all that is known about its detrimental effects on many diverse aspects of human health (5). Many studies have shown that smoking also affects bone health in a negative fashion (6).…”
mentioning
confidence: 99%
“…As knowledge about the tobacco industry's behaviour grew, the tobacco control movement was spurred to achieve enormous progress in reducing tobacco use. But even highly optimistic projections suggest that the epidemic cannot be ended with current measures 7 8…”
mentioning
confidence: 99%
“…There is growing international interest in advancing the final stage of the tobacco pandemic, that is, ‘the tobacco endgame’ 1. A number of countries—New Zealand, Sweden, Ireland and multiple Pacific Island Nations—aim to achieve their respective tobacco endgames by 2025.…”
Section: Introductionmentioning
confidence: 99%